Estudo de modelo alternativo para estimação de componentes de (co)variância e predição de valores genéticos de características de crescimento em bovinos da raça Nelore - Marcondes, C. R.; Gavio, D.; Bittencourt, T. C C; Rocha, J. C M C; Lôbo, R. B.; Bezerra, L. A F; Tonhati, Humberto [UNESP] (FapUNIFESP (SciELO), 2002)
The objectives of this study were to estimate genetic parameters for non-standardized weights at nursing (PR120), at weaning (PR240), at yearling (PR365) and at post yearling (PR550), and to predict EPD's (expected progeny differences) for these traits using records from 29,769 Nellores. Covariance components and genetic parameters were estimated by mixed-model methodology, REML, using an animal model. Models for PR120, PR240, PR365 and PR455 included the random direct and maternal animal effects, the dam permanent environmental effect and the error. Fixed effects were contemporary group (CG) and age of cow at parturition (CIVP) and the covariate age of the calf at measuring. Two additional models for PR365, PR455 and PR550 analyses were used: the first included CG and CIVP, animal and maternal direct effect, residual and age of the calf (as covariate), and the second included CG and CIVP (as fixed effects), animal direct effect, residual and age of calf at measuring. Observed means±standard deviations were: 127±25kg (PR120); 191±34kg (PR240); 225±42kg (PR365); 266±51kg (PR455) and 310±56kg (PR550). From single-trait analyses, direct and maternal heritabilities for PR120, PR240, PR365 and PR455 were, respectively, .23 and .08; .19 and .10; .24 and .04; .30 and .04. Direct heritabilities were .39; .44 and .43, respectively, for PR365, PR455 and PR550. In the model without permanent effect, direct and maternal heritabilities for PR365, PR455 and PR550 were .25 and .08; .32 and .07; .38 and .03, respectively. When the estimates for standardized traits at the same period were compared, no differences in magnitude were found. Rank correlation had important changes when standardized and non-standardized traits were compared.
Alternative model to estimate (co)variance components and to predict breeding values for growth traits in Nelore cattle
Keywords: Beef cattle; Covariance; Genetic parameters; Nellore; Postweaning growth; Preweaning growth; Rank correlation; animal experiment; beef cattle; breeding; comparative study; controlled study; correlation analysis; covariance; environmental factor; genetic parameters; genetic trait; growth rate; heritability; lactation; maternal welfare; nonhuman; prediction; weaning; Animalia; Bos taurus